PENGARUH PEMAHAMAN TINDAK PIDANA KORUPSI DAN PEMAHAMAN PENGHINDARAN PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK DALAM PEMBAYARAN PAJAK DI DAERAH ISTIMEWA YOGYAKARTA - F. Christianto, Valentinus; Suyanto, Suyanto (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2014)
The background of this research is based on the frequent occurrence of cases of corruption and tax avoidance. The problem in this research is to know is there any understanding of corruption and tax avoidance understanding affect the level of tax compliance in the payment of taxes in Yogyakarta Special Region. In this study using multiple linear regression analysis method. R Square value in this study was 24.7%, the independent variables to explain the dependent variable 24.7% and the remaining 75.3% is the influence of other variables that are not observed. The conclusion of this study is based on the F test, it is known that Ho is rejected and Ha accepted, which means that there is positive and significant. Advice given to the government and tax authority to settle cases of corruption and tax avoidance. Keywords: Corruption, Tax Avoidance, Tax Compliance